Invisible Connections : An Archaeometallurgical Analysis of the Bronze Age Metalwork from the Egyptian Museum of the University of Leipzig /: An Archaeometallurgical Analysis of the Bronze Age Metalwork from the Egyptian Museum of the University of Leipzig. (2020) - Odler, Martin; Kmošek, Jiří
No abstract available